Value of Anthropometric Measurements in Predicting Difficult Laryngoscopy in Children: A Prospective, Observational Study - Gaye Aydın; Sanem Güntürk; Meltem Çakmak; Yücel Karaman; Mustafa Onur Öztan; Pervin Sutaş Bozkurt; Gizem Cabbaroğlu; Rıza Hakan Erbay (Galenos Publishing House, 2020)
INTRODUCTION: Ensuring airway security carries the utmost importance in anesthesia. Specific predictive tests or findings for difficult airway are not defined for children under 3 years old. This study is aimed at finding out the value of anthropometric measurements in the prediction of difficult laryngoscopy and intubation in children by comparing them to direct laryngoscopic evaluation of Cormack-Lehane test and intubation evaluation of Intubation Difficulty Scale.' METHODS: A total of 108 patients (aged 0-3 years), undergoing elective surgery were included in this study. Patients with known syndrome, facial anomaly, Anesthesiologists Physical Status Classification Class >2, and laryngeal mask airway were excluded from the study. Demographic data, head circumference, weight, height measurements, body mass index and percentile values were recorded by a pediatric surgeon in the preoperative period. During laryngoscopy and intubation evaluations were made using Cormack-Lehane Score and Intubation Difficulty Scale and recorded by a blinded resient. All recorded parameters were compared with Cormack-Lehane and Intubation Difficulty Scale scores. RESULTS: When all parameters were compared with CL Grade I-II-III, IDS scores; a statistically significant difference was found between age and head circumference and CL Grade I, II (p<0.05, p<0.05). When all parameters were compared in terms of difficult and easy direct laryngoscopy, relations between difficult direct laryngoscopy and male gender and low weight percentile were observed (p<0.05). Difficult intubation was not found according to Intubation Difficulty Scale. DISCUSSION AND CONCLUSION: Anthropometric measurements are not predictive for difficult direct laryngoscopy and difficult intubation in pediatric patients. The potentiality of difficult direct laryngoscopy could be higher in boys than girls and in children with low weight percentile.